(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2026)
Prolonged tuber dormancy in yam (Dioscorea spp.) is crucial for storage and economic benefits but hinders production and improvement efforts. Understanding dormancy regulation is necessary for genetic manipulation to enhance postharvest management. This study, using tuber meristematic tissues of three yam cultivars – CRI-Ahoɔdenfoɔ (D. alata), Pona and Labreko (D. rotundata) investigated the influence of endogenous gibberellic acid (GA3) and the enzymes α- and β-amylase on tuber dormancy and sprouting over 90 days of storage. Sprouting occurred at the proximal end of the tubers and coincided with a significant increase in β-amylase activity and maltose levels in the D. rotundata and D. alata cultivars at 60 and 90 days after harvest (DAH), respectively. Starch content decreased during storage. α-Amylase activity increased initially, peaking at 30 DAH, before declining and then rising again during the later storage period. The study established that yam tuber dormancy could be maintained by keeping GA3 content below a threshold limit of 1.8 mg/g, and restricting β-amylase activity to less than a 2.5-fold increase compared to harvest values. The results suggest that dormancy is regulated by a combination of GA3 and β-amylase activity in the meristematic layer of tubers, with GA3 likely inducing α-amylase synthesis for enhanced glucose generation, and β-amylase producing more maltose.